Later the House Stood Empty - Draper, Melina (Book collections on Project MUSE., 2014)
"Later the House Stood Empty mines personal and historical recollections of life on the banks of the Río de la Plata, charting a path lit by small fires of memory, weaving through time and history, to form a portrait of place and longing"--